Problem-Based Learning with Environmental Integration: An Action Research Study on Fifth-Grade Indonesian Language Achievement - Miftahul Hidayati; Rizal Rizal; Muhammad Aqil; Kadek Hariana; Muhammad Fasli; Surahman Wilade (Papanda Publisher, 2026)
Student learning outcomes in Indonesian language subjects remain suboptimal in rural elementary schools, necessitating pedagogical innovations that leverage locally available resources. This study examined the effectiveness of implementing a Problem-Based Learning (PBL) model assisted by environmental resources in improving Indonesian language learning outcomes among fifth-grade students. This classroom action research employed the Kemmis and McTaggart spiral model across two cycles at SDN 3 Sirenja, involving nine fifth-grade students. Data were collected through structured observation protocols documenting teacher and student activities, field notes, and criterion-referenced achievement tests. Quantitative data were analyzed using descriptive statistics to determine individual absorption rates and classical learning mastery, while qualitative data underwent thematic analysis following Miles, Huberman, and Saldaña's framework. Classical learning completeness increased dramatically from 11.11% at baseline to 88.88% in Cycle II, exceeding the institutional standard of 80%. Classical absorption rates improved from 32.22% to 80%, while teacher activity increased from 80.64% to 87.17% and student activity rose from 71.42% to 87.90%, indicating transformed classroom dynamics. The findings demonstrate that environment-assisted PBL significantly enhances Indonesian language learning in rural contexts by transforming passive instruction into active, student-centered learning. This approach offers a sustainable pedagogical model for resource-constrained schools, leveraging local environmental resources rather than requiring expensive materials or technology infrastructure.